Concomitant left atrial appendage closure with left ventricular assist device surgery can reduce ischemic cerebrovascular accidents. (3rd October 2022) - Nishida, H; Jeevanandam, V; Salerno, C; Song, T; Onsager, D; Nguyen, A; Grinstein, J; Chung, B; Smith, B; Kalantari, S; Sarswat, N; Kim, G; et al.
Abstract: Background: It remains unknown if concomitant left atrial appendage closure (LAAC) at the time of left ventricular assist device (LVAD) surgery can reduce ischemic cerebrovascular accidents. Purpose: The purpose of this study is to assess the impact of LAAC at LVAD surgery on the incidence of ischemic cerebrovascular accidents. Methods: Between January 2012 and November 2021, 310 patients underwent LVAD surgery with HeartMate II or III. Out of 310 patients, 98 patients (31.6%) underwent concomitant LAAC. The cohort was divided into two groups: patients with LAAC (Group A, n=98) and without LAAC (Group B, n=212). To minimize device bias, LVAD surgery with HeartWare HVAD device was excluded. The ischemic cerebrovascular accident was defined as ischemic stroke, hemorrhagic stroke or transient ischemic attack. We reviewed early and long-term clinical outcomes. The incidence of ischemic cerebrovascular accidents was compared between two groups using the Kaplan-Meier method. We also investigated if LAAC was associated with ischemic cerebrovascular accidents by Cox proportional hazards analysis. Results: There were no significant differences in baseline characteristics between two groups including age (Group A: 55.0±12.3 years old, Group B: 56.9±14.1 years old, p=0.26), preoperative CHADS2 score (Group A: 2.40±1.1, Group B: 2.58±1.1, p=0.19) and history of atrial fibrillation (Group A: 42.9%, Group B: 42.5%, p=0.95). In-hospital mortality was not significantly different between the two groups (Group A: 7.1%, Group B: 12.3%, p=0.16). In terms of postoperative complications, there were no significant differences between two groups in requiring extracorporeal membrane oxygenation, re-exploration for bleeding and newly required hemodialysis. Median follow up period was 474 days. Thirty-five patients (11.2%) developed ischemic cerebrovascular accidents (5 patients in Group A and 30 patients in Group B). The rate of freedom from ischemic cerebrovascular accidents in Group A (94.1% at 500 days and 94.1% at 1500 days) was significantly higher than that in Group B (88.2% at 500 days and 77.4% at 1500 days; log rank=0.024). In a Cox proportional hazards regression analysis including LAAC, age, history of atrial fibrillation, diabetes mellitus and Heartmate 3 device implantation, LAAC was associated with reducing the incidence of ischemic cerebrovascular accidents (hazard ratio 0.37, 95% CI 0.13–0.89, p=0.02). Conclusion: Concomitant LAAC at the time of LVAD surgery can reduce ischemic cerebrovascular accidents without increasing perioperative mortality and complications. Funding Acknowledgement: Type of funding sources: None.